Comparative Assessment the Development of Stock Market in the UK and Germany in the Face of New Challenges the COVID-19 Pandemic - Lyashenko, V.; Novikova, T.; Babenko, M. (IJAAR, 2022)
The accumulation and redistribution of financial resources is one of the conditions for the efficiency of economic activity, economic development, and the successful functioning of all sectors of the economy. Among the main instruments for such accumulation and redistribution, one can use stock market instruments or instruments of the banking sector of the economy. We settled on stock market instruments. However, in order to effectively manage financial resources, it is necessary to carry out a comprehensive analysis of the data that we have. This is especially important when there are global transformations of the economy under the influence of various factors of influence. One such factor is the development of the COVID-19 pandemic. The COVID-19 pandemic affects all areas of economic life, including the sphere of financial resource management. For the corresponding analysis, we have chosen the methodology of wavelet analysis. We applied the wavelet coherence estimation method for data analysis. The paper considers real data and real estimates for the analysis of the stock markets of the UK and Germany in the context of the development of the COVID-19 pandemic. Various graphs and diagrams are presented to understand the processes that are being investigated.
Keywords: stock market; wavelet analysis